Ocena procesu założycielskiego oraz analiza rozwoju Firmy Transportowo Handlowej Kazimierz Czosnyka - Czosnyka, Bartosz (My University, 2015)
Praca pod tytułem Ocena procesu założycielskiego oraz analiza rozwoju Firmy Transportowo Handlowej Kazimierz Czosnyka zawiera zagadnienia z zakresu przedsiębiorczości w gospodarce oraz rozwoju firmy. Na przykładzie Firmy Transportowo-Handlowej pokazuje kroki jakie podejmowała firma w celu dobrego funkcjonowania na przestrzeni swojego istnienia

This disseration titled "Evaluation of founding process and development's analysis of Kazimierz Czosnyka's transport- trade company" include issues from the entrepreneurship fild in the economy and the development of the firm. On the example of The Transport and Trade Firm, the dissertation hows the steps which were undertaken by the firm to gain appropriate functionong during exist.
Evaluation of founding process and development's analysis of Kazimierz Czosnyka's transport- trade company
Keywords: przedsiębiorstwo; biznes plan; rozwój firmy; ocena rozwoju; mikroekonomia; prawo finansowe; zarządzanie przedsiębiorstwem; ekonomia; marketing; strategia; konkurencja; otoczenie organizacji; cykl życia organizacji; zdobywanie rynku; restrukturyzacja; dywersyfikacja; company; bussiness plan; developement of the company; evaluation of development; microeconomics; financial law; business management; economics; marketing; strategy; competition; business environment; life course of organsation; extraction of the market; overhaul; diversification